The Effect Of Cerdas Learning Model On The Result Of Students’ Natural Science - Noviani, Ketut Ari; Agustiana, I Gusti Ayu Tri (Universitas Pendidikan Ganesha, 2020)
The problem of this research was the lack of teachers in using innovative learning that affects studens’t learning outcomes. This research aimed to determine the effect of the “CERDAS